MODEL OF ASSESSING TOTAL FINANCE RISK IN CONTROLLED DEALS ON IN-GROUP FINANCING - Maxim G. Nagornykh (Вестник Российского экономического университета имени Г. В. Плеханова)
In conditions of current development of taxation policy in Russia the activity of interrelated companies is connected with serious financial risks arising in the result of government control over their deals. It stipulates topicality and necessity to design in-house methodology for handling controlled deals. The author demonstrates theoretical and methodological approaches to designing the model of assessing the total finance risk in controlled deals. The present model was designed with due regard to the effective practice of taxation and principles of state regulation of controlled deals of companies, whose subject is granting in-group loans and credits.